Regarding the efficiency of complex steel deoxidation - Шульга, Виктор Олегович (Technology audit and production reserves, 2013)
The mechanism of carbon removal at the initial stage of processing the chromium steel scrap was considered. The results of thermodynamic analysis of the processes of decarbonization and deoxidation of steel were given. For improving the deoxidation efficiency, physical-chemical analysis of combinations of metals and their interactions with the dissolved in the melt oxygen was made. Complex deoxidizers based on aluminum with silicon and barium are quite effective. Thus, the possibility to increase the efficiency of the complex based on metal with lower affinity for oxygen from the metals with higher affinity for oxygen of a series of affinities was established. Explanation of the obtained results based on the model which takes into account the equilibrium of reactions between the metal-deoxidizer and dissolved oxygen was proposed. The use of complex deoxidizer improves the kinetics of deoxidation and reduces the number of non-metallic inclusions.